Design Procedure of a Mono-Anchor Head for 2360 MPa High-Strength Steel Strand - Sang-Woo Ko; Jin-Kook Kim (Applied Sciences, 2023)
In this paper, a design procedure for a mono-anchor head anchoring a 2360 MPa high-strength steel strand is proposed. The performance criteria of the existing anchor head based on PTI (Post-Tensioning Institute) have been reorganized so that they can be evaluated based on the plastic hoop strain appearing at the top of the wedge hole. In order to design a mono-anchor head that does not exceed the permissible performance standard, the stress and deformation mechanisms of the mono-anchor head were investigated. It was confirmed that the external force was locally concentrated at the top of the wedge hole due to the interaction between the components of the anchorage device. An investigation based on the finite element method was conducted to identify the degree of external force concentration at the location and establish the relationship with the plastic hoop strain. An analytical investigation was conducted according to the design variables of the mono-anchor head, and in this process, static load tests and material tests were conducted to create an analytical model that reflects the actual behavior of the anchorage system. An equation was established regressionally so that the plastic hoop strain, which is a performance criterion, can be calculated according to the configuration and yield strength of the anchor head. Following the proposed design procedure, the configuration can be properly determined when the yield strength determination is limited due to material supply and demand. In addition, when space is limited during the construction of an anchorage device, the dimensions of an anchorage device in a small size can be determined, and the yield strength appropriate for that size can be determined.